KEMANDIRIAN USAHA MIKRO MELALUI STRATEGI PEMBERDAYAAN DALAM PENGELOLAAN ZAKAT PRODUKTIF LEMBAGA AMIL ZAKAT: ANALISIS MAQASHID SYARIAH - Chasanah, Uswatun; Maspupah, Ima (Universitas KH. A. Wahab Hasbullah, 2025)
ABSTRACT Micro, Small, and Medium Enterprises (UMKM) play a crucial role in the country's economic growth. This is because UMKM can absorb a significant workforce, thereby alleviating poverty and equitable distribution of income. However, micro-enterprises still face numerous challenges to achieve business independence. One such challenge is empowering Amil Zakat Institutions (LAZ) to manage productive zakat. This productive zakat management plays a strategic role in promoting the economic independence of those entitled to receive zakat. LAZ can develop five empowerment theories and concepts: Empowerment Theory, Capacity Building Theory, Social Network Theory, Sharia Economic Theory, and the Economic Empowerment Model. Based on the author's analysis, the empowerment concepts developed by LAZ in their programs align with the objectives of sharia law: safeguarding religion, life, family, intellect, and wealth. Keywords: Micro-Enterprise Independence, Empowerment, Productive Zakat